Penerapan Prinsip-Prinsip Seni Rupa Pada Kaligrafi Di Masjid Baiturrahman Unimed - Joko Tri Utoyo; Agus Priyatno; Adek Cerah Kurnia Azis (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
This study aims to determine the results of applying the principles of fine arts to some calligraphy at the Baiturrahman Unimed mosque. This study uses the rattil method (tidying up, arranging, order) to find out how deep the application of the principles of art used in calligraphy, and the type of calligraphy used. Calligraphy that is taken for research uses a qualitative descriptive method in which the researcher will describe and describe all aspects related to proportion, balance, rhythm, clarity, and unity. So with this method it will be known about the principles of art and design in calligraphy. This research instrument uses a camera and scanner as documentation and an assessment sheet in the form of a table of indicators based on the principles of fine arts which is limited to only five (5) aspects. Data collection techniques are carried out by making observations, documentation, and literature studies related to the research topic. And from the sample taken, it is known that the type of khat used is the Naskhi, Riq'ah, and Tsuluts khat. Overall the application of the principles of fine art in calligraphy at the Baiturrahman Unimed mosque has elements from the value of the proportion aspect then the aspect of balance, the aspect of rhythm, followed by the aspect of clarity, and the last aspect is the unity of the five elements, it turns out that in its application there is no wholeness and perfection elements and design which means that the application is still not good.